The Impact of Risk Preference in Decision Behavior on Urban Expansion Morphology - Zhangwei Lu; Lihua Xu; Yaqi Wu; Yijun Shi; Jinyang Deng; Xiaoqiang Shen (Complexity)
With the rapid development of urbanization, the urban expansion morphology has been changing with complex driving mechanisms behind the urban evolution process. This article simulates the results of urban land development contingent upon decision-makers’ risk preferences and reveals the inherent law of the effect of risk preferences on urban expansion morphology. Results show that cautious decision-makers lead to the urban expansion morphology being relatively compact, and the reckless decision-makers lead the urban expansion to sprawl. Moreover, there are obvious differences in strengths of planning constraints on the decision-makers with different risk preferences. The reckless decision-makers, driven by the economic interests, are more likely to break through the planning, especially when the planning is not reasonable. It is also found that enhancing executive ability of planning for the reckless decision-makers can promote compactness of the urban expansion morphology. However, the effect of enhancing executive ability of planning on the cautious decision-makers is limited. Thus, in the case of unreasonable planning, the executive ability of planning to the reckless decision-makers should be enhanced so as to avoid urban sprawl.